Study of Surface Roughness of Machined Polymer Composite Material - Zuzana Hutyrová; Jozef Zajac; Peter Michalik; Dušan Mitaľ; Ján Duplák; Stanislav Gajdoš (International Journal of Polymer Science)
The aim of this paper is to evaluate the influence of selected cutting parameters (speed of rotation and feed rate) on the surface topography of drilled WPC material. Objective of the study is to establish dependence of the surface roughness of borehole walls (parameter Rz—average maximum height) on the speed of rotation and feed rate of a drill bit. Technological parameters of experimental drilling were feed rate of 100–300 mm·min−1 and speed of rotation of 2000–6000 rpm.